OPTIMALISASI PENGGUNAAN SURVEY LINGKUNGAN BELAJAR (SULINGJAR) UNTUK MENINGKATKAN KINERJA GURU - Viosa Vironika Santika; Winar Suci Rahayu; Abdul Wahid (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
Objective: This study aims to examine the optimization of the use of the Learning Environment Survey (Sulingjar) in improving teacher performance at RA Nyatnyono 01 Semarang, with a focus on reflecting on learning practices and the implementation of the Merdeka Curriculum. Using a descriptive qualitative approach, data were collected through participatory observation over three weeks, semi-structured interviews with six teachers, and document analysis such as Sulingjar results, Education Reports, and government training reports. Data analysis referred to the interactive model of Miles and Huberman (1994), including data reduction, data presentation, and conclusion drawing with triangulation to ensure validity. The results showed that Sulingjar helped teachers reflect on and improve their lesson planning, increase the variety of teaching methods, and support the implementation of the student-centered Merdeka Curriculum. However, obstacles such as administrative burdens, limited digital literacy, and a lack of systematic follow-up from the Education Report hindered optimization. This study concludes that Sulingjar has the potential to be a tool for educational transformation if it is supported by technical training and better integration with teacher development programs, thereby strengthening teacher performance and learning quality in accordance with National Education Standards.